EFFECT OF STORAGE OF HATCHING EGGS ON HATCHING PERFORMANCE OF VARIOUS TYPES OF LOCAL POULTRY: A REVIEW - D., PRIYAMBODO; AFNAN, R.; ULUPI, N.; ., HARIONO (Majalah Ilmiah Peternakan; Vol 27 No 1 (2024): Vol. 27 No. 1 (2024)DO - 10.24843/MIP.2024.V27.i01.p03, 2024)
Storing hatching eggs is one of the stages carried out before the hatching process. Storing hatching eggs is car- ried out to adjust the number of eggs to the maximum capacity of the hatching machine. Many studies have been carried out on storage treatments for hatching eggs of various local poultry, but not many have summarized the results of these studies. This review article aims to discuss the effects of storage treatments for hatching eggs before hatching on hatching performance in various types of local poultry. This article was created by synthesizing and analyzing secondary data from various sources from reputable national and international accredited journals whose theme concerns the treatment of hatching egg storage on hatching performance. The results of research on storing hatching eggs of various types of local poultry with a hatchability percentage of more than 70% can be obtained by storing hatching eggs for 7 days at room temperature. Hatchability can be increased if the storage room tempera- ture can be set to less than 200C.